Exploratory Survey at the Mexican Marketplace on Pork Muscles Characteristics From U.S.A. and Mexico - Méndez Medina, Rubén Danilo; Ponce Alquicira, Edith; Rubio Lozano, María Salud; Ryan, Suzanne; Huerta Leidenz, Nelson (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
Trends in variation of physical, chemical and sensory traits due to country of origin (COO) were evaluated for samples from United States of America (U.S.A.) and Mexico of three pork muscles, Rectus femoris (RF, n = 20 from each COO), Vastus medialis (VM, n = 20 from each COO), and Longissimus dorsi (LD, n = 10 from each COO) in two separate, small-scale, exploratory surveys conducted at Mexico City. Compositional, physical and chemical properties and consumer acceptability traits of these Mexican and U.S.A. pork samples were quite similar, though Mexican pork samples generally were more variable. LD samples from U.S.A. had greater (P